(untitled) (PerCursos, 2023)
Assuming the intimate relations between nature and politics, this text analyzes the narratives and processes by which certain cosmopolitics relate in the geological epoch of the Anthropocene. Departing from recent news of a “climate crisis”, or “planetary catastrophe”, or “end of the world”, we present initially an a discussion about truth and denialism, relating it to a fictional ethics. Subsequently, aiming to emphasize composition as a strategy for shifting the centrality of certain knowledges which roots are set in modern paradigms, we gather the perspectives from ecological, amefrican and amerindian ways of thinking, in order to reflect about the incidences of such problems in a Brazilian context.